Model systems for papillomavirus-associated skin disease. (2020) - Dorfer, Sonja; Handisurya, Alessandra
Abstract : Papillomaviruses (PVs) are small, non-enveloped, double-stranded DNA tumor viruses, which target epithelial cells of the skin and mucosa of different vertebrate species, including humans, for infection. To date, more than 230 human papillomavirus (HPV) types are known according to the PapillomaVirus Episteme (PaVE) database and classified into 5 different genera, alpha, beta, gamma, mu and nu [1] . Preclinical model systems that mimic HPV infections are essential tools for investigations on viral etiology and pathophysiological processes of human diseases. Herein, we describe different PV infection model systems in animals, focusing on models for skin carcinogenesis.